Drosophila miR-277 controls branched-chain amino acid catabolism and affects lifespan. - Esslinger, S.M.; Schwalb, B.; Helfer, S.; Michalik, K.M.; Witte, H.; Maier, K.C.; Martin, D.; Michalke, B.; Tresch, A.; Cramer, P.; Förstemann, K. (RNA Biology., 2013)
Development, growth and adult survival are coordinated with available metabolic resources, ascertaining that the organism responds appropriately to environmental conditions. MicroRNAs are short (21-23 nt) regulatory RNAs that confer specificity on the RNA-induced silencing complex (RISC) to inhibit a given set of mRNA targets. We profiled changes in miRNA expression during adult life in Drosophila melanogaster and determined that miR-277 is downregulated during adult life. Molecular analysis revealed that this miRNA controls branched-chain amino acid (BCAA) catabolism and as a result it can modulate the activity of the TOR kinase, a central growth regulator, in cultured cells. Metabolite analysis in cultured cells as well as flies suggests that the mechanistic basis may be an accumulation of branched-chain ?-keto-acids (BCKA), rather than BCAAs, thus avoiding potentially detrimental consequences of increased branched chain amino acid levels on e.g., translational fidelity. Constitutive miR-277 expression shortens lifespan and is synthetically lethal with reduced insulin signaling, indicating that metabolic control underlies this phenotype. Transgenic inhibition with a miRNA sponge construct also shortens lifespan, in particular on protein-rich food. Thus, optimal metabolic adaptation appears to require tuning of cellular BCAA catabolism by miR-277.